Late Quaternary Chrysophycean stomatocysts in a Southern Carpathian mountain lake, including the description of new forms (Romania) - Soróczki˗pintér, Éva; Pla˗rabes, Sergi; Magyari, Enikő Katalin; Stenger-Kovács, Csilla; Buczkó, Krisztina (Phytotaxa, 2014)
In this study we present results of a low-resolution chrysophyte stomatocyst analysis that followed a high-resolution diatom analysis of a mountain lake sediment sequence from the Retezat Mountains, in the south Carpathians (Romania). The stomatocyst assemblages of the previously distinguished ten diatom assemblage zones of Lake Gales were studied with the aim to describe stomatocyst composition and create a taxonomical basis for detailed stratigraphical analysis in the future. We report 83 stomatocyst forms, and 7 of them are formally described here as new for science. An abrupt shift in cyst as well as diatom assemblages were recorded around 9200 cal yr BP during the 15,000 years long history of the Lake Gales. This Lake Gales event could be linked to the 9.3-ka widespread significant climatic anomaly, which was triggered by a melt water pulse into the North Atlantic.